DOI: 10.26756/th.2012.29
|View full text |Cite
|
Sign up to set email alerts
|

A study of the alignment between the Lebanese secondary-level national math exams for the literature and humanities track and the reformed math curriculum. (c2012)

Abstract: Curriculum alignment is a systematic process to ensure strong congruency among the three curriculum aspects: the written, the taught, and the tested curricula. The purpose of this study was to investigate the alignment between the official exams for the "Literature and Humanities" track of the secondary school education and the Lebanese reformed math curriculum. The method is both qualitative and quantitative. Semi-structured interviews were conducted with two test developers of math official exams for grade 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(20 citation statements)
references
References 13 publications
1
18
0
1
Order By: Relevance
“…Terdapat berbagai metode untuk menganalisa keseuaian antara standar dengan pembelajaran. Namun, dalam penelitian ini metode analisis yang digunakan adalah metode Porter sebab metode ini lebih mudah diaplikasikan karena terdapat kriteria yang jelas dalam menganalisis keselarasan (Smithson, 2009;Sleiman, 2012;Arliani, E & Hidayati, 2013;Firman, 2013;Oktariani;Firman, 2014;Oktariani, O., & Febliza, 2019). Selain tingkat keselarasan indeks keselarasan juga akan terungkap perbedaan dari segi konten materi maupun tuntutan kemampuan kognitif (Roach et.…”
Section: Journal Of Research and Education Chemistry (Jrec)unclassified
“…Terdapat berbagai metode untuk menganalisa keseuaian antara standar dengan pembelajaran. Namun, dalam penelitian ini metode analisis yang digunakan adalah metode Porter sebab metode ini lebih mudah diaplikasikan karena terdapat kriteria yang jelas dalam menganalisis keselarasan (Smithson, 2009;Sleiman, 2012;Arliani, E & Hidayati, 2013;Firman, 2013;Oktariani;Firman, 2014;Oktariani, O., & Febliza, 2019). Selain tingkat keselarasan indeks keselarasan juga akan terungkap perbedaan dari segi konten materi maupun tuntutan kemampuan kognitif (Roach et.…”
Section: Journal Of Research and Education Chemistry (Jrec)unclassified
“…A better explanation for this good performance is perhaps what Squires (2012) and Schmidt et al (2001) highlighted, referring to TIMSS results, maintaining that the more a class spends on a topic, the better achievement they'll have on that topic, especially if the curriculum and assessment are mostly based on drill and practice. Sleiman (2012) and Safa (2013) studied the math national tests for LH and LS secondary level respectively, under the 1997 reformed curriculum, until the years 2010 and 2012 respectively. Several national examinations were held since then till the present time.…”
Section: Lebanon's Results On Timss Assessment For Grades 8 and 12mentioning
confidence: 99%
“…-semi-structured interviews with two members of the national-tests developing committee, -a content analysis of the following: o the general and specific objectives (ECRD, 1997a) For the above analyses, Sleiman classified the test items according to a two-entry matrix, the content domains and the TIMSS's three cognitive domains, "Knowing", "Applying" and "Reasoning". Results showed that the national tests are reasonably aligned, over the years 2001-2010, with the reformed curriculum in terms of the math domains tested, but they considerably lack alignment with the curriculum's general objectives and cycle's specific objectives (Sleiman, 2012). The tests focus most on the "knowing" and "applying" cognitive domains and neglect other more important general objectives: mathematical reasoning, problem solving, communication, and connections.…”
Section: Studies On the Alignment Of The Lebanese Curriculummentioning
confidence: 99%
See 2 more Smart Citations